PEMBENTUKAN TEACHER PROFESSIONAL IDENTITY MAHASISWA MELALUI PENGALAMAN PRAKTIK LAPANGAN PERSEKOLAHAN (PLP 2) SEBUAH COLLABORATIVE AUTOETHNOGRAPHY - Fira Safitri; Muhammad Idris; Feni Febrianti; Fera Periska; Siska Juliana; Andi Rayong; Adit Armin; Gina Indriani; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School Field Practice (PLP 2) is an important stage in teacher education because it provides prospective teachers with direct experience in the learning process at schools. This study aims to analyze the formation of students’ Teacher Professional Identity through their experiences during PLP 2. The research employed a qualitative approach using the Collaborative Autoethnography method. Data were collected through daily reflective journals, teaching experience notes, weekly reflections, and students’ subjective narratives during the field practice program. Data analysis was conducted thematically through data reduction, theme categorization, reflective interpretation, and conclusion drawing. The findings indicate that students encountered various pedagogical, emotional, and social challenges during PLP 2. Pedagogical challenges included difficulties in classroom management, delivering learning materials, and building active interaction with students. Emotional challenges were reflected in feelings of nervousness, lack of self-confidence, and mental pressure when facing classroom situations. Meanwhile, social challenges were related to adapting to school culture and communicating with mentor teachers and students. Through these experiences, students gradually developed their professional identity as prospective teachers through self-reflection, experience evaluation, and increased awareness of professional responsibilities. Therefore, PLP 2 plays an important role in shaping students’ professional readiness and teacher professional identity.